Hydrate phase transition and seepage mechanism during natural gas hydrates production tests in the South China Sea: A review and prospect - Xu-wen Qin; Cheng Lu; Ping-kang Wang; Qian-yong Liang (China Geology, 2022)
ABSTRACT: Natural gas hydrates (NGHs) are globally recognized as an important type of strategic alternative energy due to their high combustion efficiency, cleanness, and large amounts of resources. The NGHs reservoirs in the South China Sea (SCS) mainly consist of clayey silts. NGHs reservoirs of this type boast the largest distribution range and the highest percentage of resources among NGHs reservoirs in the world. However, they are more difficult to exploit than sandy reservoirs. The China Geological Survey successfully carried out two NGHs production tests in the Shenhu Area in the northern SCS in 2017 and 2020, setting multiple world records, such as the longest gas production time, the highest total gas production, and the highest average daily gas production, as well as achieving a series of innovative theoretical results. As suggested by the in-depth research on the two production tests, key factors that restrict the gas production efficiency of hydrate dissociation include reservoir structure characterization, hydrate phase transition, multiphase seepage and permeability enhancement, and the simulation and regulation of production capacity, among which the hydrate phase transition and seepage mechanism are crucial. Study results reveal that the hydrate phase transition in the SCS is characterized by low dissociation temperature, is prone to produce secondary hydrates in the reservoirs, and is a complex process under the combined effects of the seepage, stress, temperature, and chemical fields. The multiphase seepage is controlled by multiple factors such as the physical properties of unconsolidated reservoirs, the hydrate phase transition, and exploitation methods and is characterized by strong methane adsorption, abrupt changes in absolute permeability, and the weak flow capacity of gas. To ensure the long-term, stable, and efficient NGHs exploitation in the SCS, it is necessary to further enhance the reservoir seepage capacity and increase gas production through secondary reservoir stimulation based on initial reservoir stimulation. With the constant progress in the NGHs industrialization, great efforts should be made to tackle the difficulties, such as determining the micro-change in temperature and pressure, the response mechanisms of material-energy exchange, the methods for efficient NGHs dissociation, and the boundary conditions for the formation of secondary hydrates in the large-scale, long-term gas production.©2022 China Geology Editorial Office.